2020
DOI: 10.1111/odi.13318
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of prognostic nutritional index in patients with oral squamous cell carcinoma

Abstract: Objectives To determine the prognostic significance of preoperative prognostic nutritional index (PNI) in patients with primary oral squamous cell carcinoma (OSCC) after ablative surgery. Materials and Methods A total of 333 patients from two tertiary referral centers were enrolled as training and validation cohorts. The PNI was calculated as 10× serum albumin (g/dL) + 0.005 × total lymphocyte number (per mm3), and its optimal cutoff value for patient stratification was identified by X‐tile software. Cox's pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…More and more researches indicate systemic nutrition has been found to be a crucial ingredient of the tumor microenvironment that plays remarkable roles in tumor growth, progression and metastasis 2 . For patients with malignant tumors, the tumor itself will consume a lot of protein, causing damage to tissue structure and organ functions; in addition, gastrointestinal obstruction caused by digestive organ tumors can lead to loss of appetite, nausea, vomiting, diarrhea which is also associated with poor nutrition and immunosuppression 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…More and more researches indicate systemic nutrition has been found to be a crucial ingredient of the tumor microenvironment that plays remarkable roles in tumor growth, progression and metastasis 2 . For patients with malignant tumors, the tumor itself will consume a lot of protein, causing damage to tissue structure and organ functions; in addition, gastrointestinal obstruction caused by digestive organ tumors can lead to loss of appetite, nausea, vomiting, diarrhea which is also associated with poor nutrition and immunosuppression 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generally set the cut-off OPNI for various types of malignancies at 45, because an OPNI <45 has been regarded as malnutrition and correlated to the risk of postoperative complications [ 15 ]. In surgical cases with head and neck cancer including OSCC, Wu et al reported that the optimal OPNI cut-off was 47.4 [ 8 ]. In a large-scale prospective study, Bao et al reported a cut-off of 49.3, which correlates with poor OS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence has shown that low OPNI is related to poorer prognoses in various types of cancers [ [5] , [6] , [7] ]. In OSCC, Wu et al evaluated the predictive performance of OPNI and reported that low preoperative OPNI was significantly related to a poor prognosis and serves as a novel prognostic biomarker [ 8 ]. Similarly, Bao et al reported the predictive value of OPNI, along with other nutritional indicators such as body mass index, serum albumin, and the nutritional risk index [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lymphocyte counts (L), lymphocyte-monocyte ratio (LMR), neutrophil-lymphocyte ratio (NLR), plateletlymphocyte ratio (PLR), systemic immune-inflammation index (SII), prognostic nutritional index (PNI), and C-reactive protein (CRP) have been developed and verified with prognostic values in a broad spectrum of cancers (8)(9)(10)(11)(12). In our previous studies, high SII and plateletneutrophil-lymphocyte score (PNL), low PNI, high counts of platelets and neutrophils, and low lymphocyte counts were significantly associated with reduced survival in patients with resectable OSCC (12)(13)(14). In addition, most cancer-induced profound metabolic and physiological alterations that undermine patients' nutritional status and nutrient intake have been found to ultimately result in severe malnutrition and cachexia (15).…”
Section: Introductionmentioning
confidence: 97%